2020
DOI: 10.1039/d0lc00096e
|View full text |Cite
|
Sign up to set email alerts
|

A web-based automated machine learning platform to analyze liquid biopsy data

Abstract: We have developed a web-based, self-improving and overfitting-resistant automated machine learning tool tailored specifically for liquid biopsy data, where machine learning models can be built without the user's input.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…In the past decade, more and more attention has been paid to deep learning. Compared to traditional machine learning, deep learning has shown its merits in microbiological analysis [ 26 , 27 , 28 , 29 ], such as strong learning ability, good adaptability and excellent performance. A typical example of deep learning was reported by Kanakasabapathy et al [ 30 ] for the detection of embryos using inexpensive automated deep learning-based imaging systems, and more than 90% of embryos were successfully classified.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, more and more attention has been paid to deep learning. Compared to traditional machine learning, deep learning has shown its merits in microbiological analysis [ 26 , 27 , 28 , 29 ], such as strong learning ability, good adaptability and excellent performance. A typical example of deep learning was reported by Kanakasabapathy et al [ 30 ] for the detection of embryos using inexpensive automated deep learning-based imaging systems, and more than 90% of embryos were successfully classified.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this approach allowed the researchers to predict recurrence-free survival (RFS). Shen et al . developed an automated web-based ML (AutoML) tool where models can be built without the user’s input.…”
Section: The Future: Automation and Artificial Intelligencementioning
confidence: 99%
“…Interestingly, this approach allowed the researchers to predict recurrence-free survival (RFS). Shen et al 118 developed an automated web-based ML (AutoML) tool where models can be built without the user's input. The approach was further validated by performing a meta-analysis on 11 independent published data sets and found that we had similar or better performance compared to those reported in the literature.…”
Section: ■ Challenges: Clinical Implementationmentioning
confidence: 99%
“…[ 89 ] For example, an automated machine learning platform to analyze liquid biopsy data has been recently reported. [ 90 ] It was specifically designed for liquid biopsy data and has the very interesting capability to continuously improve itself as the quantity of the processed liquid biopsy data increases.…”
Section: Circulating Tumor Biomarkersmentioning
confidence: 99%